Coins from south of the North Gate of Jerash. (4th May 2021) - Shiyyab, Adnan; Bauzou, Thomas
Abstract : This article is a descriptive and analytical study of a group of bronze coins discovered in the northern part of Jerash. The aim of this study is to shed light on the history of this part of the city through the coins. The result of this analysis shows that these coins represent the historical periods, starting with the Greek, followed by the Nabataean, Roman and finally early Islamic period. It is noticeable that Greek, Nabataean and Islamic coins are few in number and represent only a very small percentage of the total; Romans coins account for the vast majority. An important point of note is the absence of Byzantine coins within the group.